2009
DOI: 10.1007/s00374-009-0429-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of ergosterol, microbial biomass C, N, and P after steaming as a result of sucrose addition, and Sinapis alba cultivation

Abstract: A pot experiment was carried out to monitor the recovery of a steaming-reduced microbial biomass (C, N, and P) and fungal ergosterol by sucrose addition. The second objective was to investigate the recovery of a steaming-reduced microbial biomass by white mustard (Sinapis alba) cultivation and its interactions with microbial residues, freshly formed from sucrose addition. Thirty days after steaming, the soil microbial biomass C and N was still significantly reduced by 80%, leading to a rather constant microbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The microbial residues, which comprise microbial exoenzymes, mucous substances, and dead microbial tissue (Khan et al 2010), were calculated as maize-derived soil organic C without POM-C and maize-derived microbial biomass C. Statistical analyses were carried out using SPSS statistical software (SPSS 15.0). The significance of experimental effects was tested by a two-way ANOVA in tables and by a one-way ANOVA in figures using the least significant difference (LSD) test (P<0.05).…”
Section: Calculations and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The microbial residues, which comprise microbial exoenzymes, mucous substances, and dead microbial tissue (Khan et al 2010), were calculated as maize-derived soil organic C without POM-C and maize-derived microbial biomass C. Statistical analyses were carried out using SPSS statistical software (SPSS 15.0). The significance of experimental effects was tested by a two-way ANOVA in tables and by a one-way ANOVA in figures using the least significant difference (LSD) test (P<0.05).…”
Section: Calculations and Statistical Analysismentioning
confidence: 99%
“…Non-mycorrhizal mutants can be an important tool for studies on the interactions between AMF and other rhizosphere microorganisms without the demand for soil sterilization (Endlweber and Scheu 2006;Vestergård et al 2008) or pasteurization (Endlweber and Scheu 2006), which have strong impacts on soil chemistry and soil biology, by mobilizing nutrients such as N and P (Kahiluoto et al 2000;Endlweber and Scheu 2006) and by killing many other soil organisms (Khan et al 2010). The myc − mutants as nonmycorrhizal controls are available for tomatoes (Cavagnaro et al 2006) but also for peas (Duc et al 1989;Kleikamp and Joergensen 2006).…”
Section: Introductionmentioning
confidence: 99%
“…2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim www.plant-soil.com High application rates of mucilage increased root N content due to the depressive effects on plant growth. Not only may the high polyphenol content of coffee mucilage has depressive effects on plant growth (Contreras-Porras and Del Aguila, 2011), but high concentrations of easily soluble carbohydrates have also been repeatedly shown to reduce plant growth (Sulmon et al, 2007;Nieminen, 2009;Khan et al, 2010). However, any plant growth-depressing effects of coffee mucilage might be useful to reduce weed-growth near coffee plants, above a certain threshold in height.…”
Section: Plant Developmentmentioning
confidence: 99%
“…Soil steam disinfection (SSD) technology can efficiently kill fungi, bacteria, and pests under the condition of soil cultivation for facility agriculture [1][2][3][4], which can solve the problem of continuous 2 of 22 cropping in high-value crop cultivation [5][6][7]. Experts around the world found that the injection SSD method has the advantage of higher heating rate for deep soil [6][7][8][9][10][11][12][13][14][15]. But for the disinfection of clay-loam in Yangtze River delta (China), because of its soil clay content and small soil pores which cause poor water permeability [16,17], the SSD injection method under clay-loam conditions will seriously affect the diffusion range of steam in the dense soil [18,19], resulting in poor disinfection efficiency and increased energy consumption.…”
Section: Introductionmentioning
confidence: 99%